The Importance of the Body and Feeling in the Philosophy of A. Rosmini - Darós, William Roberto (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
The author of this paper highlights the priority of feeling in A. Rosmini´s philosophy. Feeling is life itself and is also the criterion of reality. But human beings cannot be reduced to the real dimension only, since they also possess an intellectual and a moral dimension. The paper analyzes the elements of the act of thinking, and clarifies the difference among sensations, fundamental (vital, substantial) feeling, and instinct (vital and sensual). It also considers the distinction between our body and its identity —insofar as it is our body— and the bodies of other persons. The paper finally analyzes some deficient philosophical definitions of the human body.